A Pluronic® F127-based polymeric micelle system containing an antileishmanial molecule is immunotherapeutic and effective in the treatment against Leishmania amazonensis infection. Issue 1 (February 2019) - Tavares, Grasiele S.V.; Mendonça, Débora V.C.; Miyazaki, Carolina K.; Lage, Daniela P.; Soyer, Tauane G.; Carvalho, Lívia M.; Ottoni, Flaviano M.; Dias, Daniel S.; Ribeiro, Patrícia A.F.; Antinarelli, Luciana M.R.; Ludolf, Fernanda; Duarte, Mariana C.; et al.
Abstract: Clioquinol (5-chloro-7-iodoquinolin-8-ol or ICHQ) was recently showed to presents an in vitro effective antileishmanial action, causing changes in membrane permeability, mitochondrial functionality, and parasite morphology. In the present study, ICHQ was incorporated into a Poloxamer 407-based polymeric micelles system (ICHQ/M), and its antileishmanial activity was in vivo evaluated in L. amazonensis -infected BALB/c mice. Amphotericin B (AmpB) and its liposomal formulation (Ambisome®) were used as controls. Parasitological and immunological evaluations were performed 30 days after the treatment. Results indicated more significant reductions in the average lesion diameter and parasite burden in ICHQ or ICHQ/M-treated mice, which were associated with the development of a polarized Th1 immune response, based on production of high levels of IFN-γ, IL-12, TNF-α, GM-CSF, and antileishmanial IgG2a antibody. Control groups´ mice produced high levels of IL-4, IL-10, and IgG1 isotype antibody. No organic toxicity was found by using ICHQ or ICHQ/M to treat the animals, although those receiving AmpB and Ambisome® have presented higher levels of renal and hepatic damage markers. In conclusion, results suggested that the ICHQ/M composition can be considered as an antileishmanial candidate to be tested against human leishmaniasis. Graphical abstract: Highlights: Amphotericin B is effective against Leishmania but toxic to mammals. This drug was used to treat against murine visceral leishmaniasis. It was administered in three delivery systems into the infected BALB/c mice. AmpB-containing Poloxamer P407®-based polymeric micelles were the most efficient. Treated and infected animals showed low parasitism, Th1 immunity and any toxicity.